2014
DOI: 10.1002/adsc.201400164
|View full text |Cite
|
Sign up to set email alerts
|

Site Selective Synthesis of Pentaarylpyridines via Multiple Suzuki–Miyaura Cross‐Coupling Reactions

Abstract: Pentaarylpyridines were conveniently prepared in one step by pentafold Suzuki-Miyaura reactions of pentachloropyridine. Moreover, site selective reactions were performed, leading to various substituted arylpyridines. Pentaarylpyridines were studied in detail by means of DFT calculations and by optical spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 53 publications
(8 reference statements)
0
54
0
Order By: Relevance
“…Parent 2,3-, 60b , 75 2,4-, 39 , 75e , 76 and 2,5-dihalopyridines, 60b , 75b , e , 76f , 77 and 2,3,5-trichloropyridine, 78 2,3,5,6-tetrachloropyridine 79 and pentachloropyridine 79 , 80 are known to preferentially undergo SMC reactions at C2/C6. 7 , 12 Whereas 4-aryl-2,3,5,6-tetrachloropyridine can undergo sequential SMC reactions at C2/C6 then C3/C5, 79 3,5-dibromo-2,6-dichloropyridine undergoes sequential SMC reactions at C3/C5 then C2/C6. 81 3,4-Dichloropyridine preferentially undergoes SMC at C4.…”
Section: Key Heteroarene Ring-systems On a Case-by-case Basismentioning
confidence: 99%
“…Parent 2,3-, 60b , 75 2,4-, 39 , 75e , 76 and 2,5-dihalopyridines, 60b , 75b , e , 76f , 77 and 2,3,5-trichloropyridine, 78 2,3,5,6-tetrachloropyridine 79 and pentachloropyridine 79 , 80 are known to preferentially undergo SMC reactions at C2/C6. 7 , 12 Whereas 4-aryl-2,3,5,6-tetrachloropyridine can undergo sequential SMC reactions at C2/C6 then C3/C5, 79 3,5-dibromo-2,6-dichloropyridine undergoes sequential SMC reactions at C3/C5 then C2/C6. 81 3,4-Dichloropyridine preferentially undergoes SMC at C4.…”
Section: Key Heteroarene Ring-systems On a Case-by-case Basismentioning
confidence: 99%
“…With substrate 3 in hand, we optimized the reaction conditions for the synthesis of monoarylpyridines 4 (Table ). As the C–I bond in postion 2 of starting material should be highly active, we started our optimization with the cheap and easily available Pd(PPh 3 ) 4 as catalyst and chose K 3 PO 4 as base and toluene as solvent based on our previous experiences with the arylation of pyridines . After some experimentation, we found that the best yield of 4a (78 %) was obtained when the reaction was carried out with Pd(PPh 3 ) 4 (5 mol‐%) as the catalyst in a solvent mixture of toluene, water and ethanol (Entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…Such approach was widely applied by many research teams in the construction of polyarylated benzenes [ 56 ], pyridines [ 57 60 ], thiophenes [ 61 – 62 ], quinoxalines [ 63 ], pyrazoles [ 64 ] pyrroles [ 65 ], pyrimidines [ 66 67 ], benzofuranes [ 68 ], imidazo[1,2- a ]pyridines [ 69 ], diaryl/heteroaryl methanes [ 70 ], and indoles [ 71 ], bearing differently substituted arene rings. An elegant approach to variously arylated pentaarylpyridines was recently proposed by Reimann et al [ 60 ]. The final outcome of such a procedure is governed by many factors, including differences in site reactivity of polyhaloarenes (concerning both regio- and chemoselectivity), reaction conditions (the nature of the palladium/ligand, temperature, base, solvents) and the steric interactions between both cross-coupling partners.…”
Section: Resultsmentioning
confidence: 99%